2008
DOI: 10.1139/z08-099
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors influencing the spatial pattern of Canada lynx relative to its southern range edge in Alberta, Canada

Abstract: We examined the spatial pattern of Canada lynx ( Lynx canadensis Kerr, 1792) relative to its southern range edge at the boreal plains – prairie ecotone in Alberta, Canada. Relative to the original distribution of boreal forest in our study area, lynx range seems to have contracted up to 22%. In 100 km2 sampling areas, lynx occupancy rate increased 1.93 times every 100 km farther (north) from the range edge that we sampled. An information–theoretic approach was used to evaluate 31 models to see which environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Some authors have speculated that, if the harvested forests are regenerated to conifer-dominated stands, lynx populations should be similar to levels in naturalorigin forests (e.g., Mowat and Slough 2003;Fuller et al 2007). The most likely negative effects of forest management on lynx populations may be reduced preferred successional habitat because of fire suppression (Mowat and Slough 2003;Steury and Murray 2004), actions that considerably reduce horizontal cover, such as pre-commercial thinning (e.g., Squires et al 2010), stand conversion from lodgepole pine to mixedwoods (Mowat and Slough 2003), and increased competition by coyotes that have expanded their range in the southern boreal (Fuller et al 2007;Bayne et al 2008a). …”
Section: Lynxmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have speculated that, if the harvested forests are regenerated to conifer-dominated stands, lynx populations should be similar to levels in naturalorigin forests (e.g., Mowat and Slough 2003;Fuller et al 2007). The most likely negative effects of forest management on lynx populations may be reduced preferred successional habitat because of fire suppression (Mowat and Slough 2003;Steury and Murray 2004), actions that considerably reduce horizontal cover, such as pre-commercial thinning (e.g., Squires et al 2010), stand conversion from lodgepole pine to mixedwoods (Mowat and Slough 2003), and increased competition by coyotes that have expanded their range in the southern boreal (Fuller et al 2007;Bayne et al 2008a). …”
Section: Lynxmentioning
confidence: 99%
“…The only study to assess oil and gas developments suggested that road density and human activity levels have had a strong negative influence on lynx populations in preferred habitats (Bayne et al 2008a). …”
Section: Lynxmentioning
confidence: 99%
“…Second, due to the nature of fur harvest data, we had to merge population time-series across large spatial areas even though this could confound differences between populations occurring at smaller spatial scales. For example, the coyote may occur in prairie regions, but the lynx does not (Bayne et al 2008). Gathering lynx and coyote data at the same spatio-temporal scales could provide a more robust test of our hypothesis, and this was the goal our traplinelevel study (see below).…”
Section: -Province-level Studymentioning
confidence: 99%
“…For example, O'Donoghue et al (1997) found that the numerical response of coyote and lynx to a snowshoe hare cycle in southwest Yukon were similar, and coyotes and lynx are the two most important mammalian predators of snowshoe hares throughout much of the boreal forest (O'Donoghue et al 1998). Furthermore, coyotes do kill lynx, and there is speculation that coyotes could influence lynx more so than does the availability of snowshoe hares (Buskirk et al 2000, Bayne et al 2008. To date, however, direct evidence supporting the negative role of interference competition on lynx populations is lacking (Murray et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the number of tracks of certain species encountered on a transect will depend on biological factors such as their abundance, food density and distribution, vegetation structure and intraspecific or interspecific interference including humans (e.g., Odonoghue et al 1997;Shapira et al 2008;Bayne et al 2008;Blaum et al 2009), but there are other classes of variables that affect the index (Buckland et al 1993). These variables are related to the observer including the observer's training and experience, eyesight and fatigue level, the environment (i.e., climatic conditions and local habitats) and aspects of the species itself such as their body size (Anderson 2001;Mackenzie and Kendall 2002).…”
Section: Introductionmentioning
confidence: 99%